2018
DOI: 10.1038/s41426-018-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific seroprevalence of human polyomavirus 12 and Saint Louis and New Jersey polyomaviruses

Abstract: The presence of specific antibodies against human polyomavirus 12, Saint Louis polyomavirus and New Jersey polyomavirus was investigated by using virus-like particle-based ELISAs with serum samples from 706 Italians aged 1- to 100-years-old. The findings indicate that these polyomaviruses circulate widely in humans, with peak seroprevalence, observed at adulthood, of 97.3%, 93.3%, 57.5%, for human polyomavirus 12, Saint Louis polyomavirus and New Jersey polyomavirus, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
14
2
Order By: Relevance
“…In contrast to our data, a very recent study reported 90% seroprevalence for HPyV12, in an Italian adult population [ 37 ]. This percentage is considerably higher than our finding and the 20% seroprevalence obtained previously for HPyV12 by Ehlers and co-workers using recombinant VP1 and VP1-based VLP ELISA [ 35 , 38 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our data, a very recent study reported 90% seroprevalence for HPyV12, in an Italian adult population [ 37 ]. This percentage is considerably higher than our finding and the 20% seroprevalence obtained previously for HPyV12 by Ehlers and co-workers using recombinant VP1 and VP1-based VLP ELISA [ 35 , 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Suboptimal HPyV12 antigen recognition, resulting from the use of a premature translation initiation site in HPyV12 VP1, causing a 16 amino acids longer version of VP1 [ 39 ], was experimentally ruled out ( S1 Fig ). Also for NJPyV a much higher seroprevalence was found in the Italian population (50%) than in our population (5%) [ 37 ]. Overall, more (sero)epidemiological studies are needed to solve these discrepancies and to define the natural host(s) of these viruses, for example by studying seroprevalence in different geographic regions while using comparable serological methods.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast to our data, a very recent study reported 90% seroprevalence for HPyV12, in an Italian adult population [36]. This percentage is considerably higher than our finding and the 20% seroprevalence obtained previously for HPyV12 by Ehlers and co-workers using recombinant VP1 and VP1-based VLP ELISA [34,37].…”
Section: Discussioncontrasting
confidence: 99%
“…Suboptimal HPyV12 antigen recognition, resulting from the use of a premature translation initiation site in HPyV12 VP1, causing a 16 amino acids longer version of VP1 [38], was experimentally ruled out (S1 Fig). Also for NJPyV a much higher seroprevalence was found in the Italian population (50%) than in our population (5%) [36]. Overall, more (sero)epidemiological studies are needed to solve these discrepancies and to define the natural host(s) of these viruses, for example by studying seroprevalence in different geographic regions while using comparable serological methods.…”
Section: Discussionmentioning
confidence: 76%
“…For instance, viral loads of human PyVs including MCPyV do not significantly differ between HIV-positive and -negative men 9 . Regarding New Jersey polyomavirus (NJPyV), which was discovered in 2014 in vascular endothelial cells of a pancreatic transplant recipient, only a few serological surveys on this virus have been reported in healthy populations and no study on HIV-positive individuals has been described to date 4,10,11 .…”
mentioning
confidence: 99%